Integrating differential expression, co-expression and gene network analysis for the identification of common genes associated with tumor angiogenesis deregulation - Monterde, Beatriz; Rojano Rivera, María Elena; Córdoba Caballero, José; Seoane Zonjic, Pedro; Perkins, James Richard; Medina-Torres, Miguel Ángel; García-Ranea, Juan Antonio (Elsevier, 2023)
Angiogenesis is essential for tumor growth and cancer metastasis. Identifying the molecular pathways involved in this process is the first step in the rational design of new therapeutic strategies to improve cancer treatment. In recent years, RNA-seq data analysis has helped to determine the genetic and molecular factors associated with different types of cancer. In this work we performed integrative analysis using RNA-seq data from human umbilical vein endothelial cells (HUVEC) and patients with angiogenesis-dependent diseases to find genes that serve as potential candidates to improve the prognosis of tumor angiogenesis deregulation and understand how this process is orchestrated at the genetic and molecular level. We downloaded four RNA-seq datasets (including cellular models of tumor angiogenesis and ischaemic heart disease) from the Sequence Read Archive. Our integrative analysis includes a first step to determine differentially and co-expressed genes. For this, we used the ExpHunter Suite, an R package that performs differential expression, co-expression and functional analysis of RNA-seq data. We used both differentially and co-expressed genes to explore the human gene interaction network and determine which genes were found in the different datasets that may be key for the angiogenesis deregulation. Finally, we performed drug repositioning analysis to find potential targets related to angiogenesis inhibition...
Keywords: Neovascularización; Regulación genética; Expresión génica; Integrative analysis; RNA-seq; Angiogenesis; Tumor angiogenesis deregulation; Gene network analysis